Investigating CRISPR spacer targets and their impact on genomic diversification of Streptococcus mutans - Walker, Alejandro R.; Shields, Robert C. (Frontiers in Genetics, 2022)
CRISPR-Cas is a bacterial immune system that restricts the acquisition of mobile DNA elements. These systems provide immunity against foreign DNA by encoding CRISPR spacers that help target DNA if it re-enters the cell. In this way, CRISPR spacers are a type of molecular tape recorder of foreign DNA encountered by the host microorganism. Here, we extracted approximately 8,000 CRISPR spacers from a collection of over three hundred Streptococcus mutans genomes. Phage DNA is a major target of S. mutans spacers. Strains have also generated immunity against mobile DNA elements such as plasmids and integrative and conjugative elements. There may also be considerable immunity generated against bacterial DNA, although the relative contribution of self-targeting versus bona fide intra- or inter-species targeting needs to be investigated further. While there was clear evidence that these systems have acquired immunity against foreign DNA, there appeared to be minimal impact on horizontal gene transfer (HGT) constraints on a species-level. There was little or no impact on genome size, GC content and ‘openness’ of the pangenome when comparing between S. mutans strains with low or high CRISPR spacer loads. In summary, while there is evidence of CRISPR spacer acquisition against self and foreign DNA, CRISPR-Cas does not act as a barrier on the expansion of the S. mutans accessory genome.